Upper bound of the second Hankel of certain class of univalent functions / Wathiqah Azaizula, Nur A’isyah Afiqah Mohd Khairi and Nur Hafizah Nur Akmal - Azaizula, Wathiqah; Mohd Khairi, Nur A’isyah Afiqah; Nur Akmal, Nur Hafizah (2023)
Geometric function theory of a complex functions makes a study of analytic univalent functions and various geometric properties of certain classes of analytic functions. Furthermore, only a few researchers are interested in discovering these function features. Next, the difficulties and problems arise when researcher selecting an accurate method. Although it gives a same result, the solution can become complicated and make researcher take time to understand whether the method use is accurate or not. Thus, the purpose of this study is to define theorem and definition of geometry functions theory and a new subclass of analytics functions and to determine the coefficient inequality of second Hankel determinant for the class of functions using method of proving by Janteng et al. (2007), Kaharudin et al. (2011) and Yahya et al. (2013).